Valuation Consequences of Clawback Provisions - Iskandar-Datta, Mai; Jia, Yonghong (The Accounting Review, 2013)
ABSTRACT: We investigate the degree to which including a clawback provision in executive compensation contracts is an effective governance mechanism by documenting the impact of clawback adoption on stock prices. We expect this ex post settling-up mechanism to be beneficial because it diminishes financial reporting risks. In support of our hypotheses, we find that the shareholders of adopting firms experience statistically significant positive stock-valuation consequences relative to propensity-score-matched control samples. Further, firms with previous financial restatements had the largest economic gains, suggesting that a clawback policy can be effective at curtailing incentives for earnings manipulation. Analysis of the bid-ask spread provides evidence that these provisions contribute to reducing financial reporting risk for restating firms, while non-restating firms experience no change in the spread. We find no evidence that clawback provisions entail costs in the form of higher CEO compensation following adoption nor do they influence the design of compensation contracts. JEL Classifications: G30; G34; G38; K12; K22. Data Availability: Data are available from sources identified in the paper.